ANALISIS KOMPARASI ATAS KINERJA DAN KEUANGAN BADAN LAYANAN UMUM BIDANG PENYEDIAAN JASA PENDIDIKAN - Yuliana Sari; Nelly Masnila; Endah Widyastuti; Riza Wahyudi (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
In its implementation, currently, efforts to provide services to the public are not optimal yet. This research is focused on BLU which provides educational service provision services, consisting of 33 state universities throughout Indonesia under the Ministry of Research, Technology and Education. The purpose of this study is to determine the development of performance and the development of financial position. From the results, it can be concluded that the performance and financial conditions of the BLU of higher education institutions in Indonesia continue to increase throughout the period 2013-2016. In addition, there are differences in performance between universities, which can be seen from the obtained surplus or deficit experienced by certain universities. This difference is suspected because between universities have a wide range of activities and different of how to manage it.